(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In a social context of rapid technological evolution, scientific research must be inspired by respect for ethical principles, to protect the human rights and freedoms of research participants and to guarantee the lawful processing of their personal data, as also established by the ethical review process of the European scientific research framework programs. However, during the research activities, ethical and legal uncertainties and criticalities may be encountered, which require particular attention and intervention to remove any obstacles and make the pursuit of scientific research purposes more efficient while respecting the rights of the participants and data subjects involved.